Brown bear feeding habits in a poor mast year where supplemental feeding occurs - Pereira, Joana (2021)
The diet of free-ranging bears is an important dimension regarding their ecology, affecting their behavior, population structure, and relation with humans. In Croatia, there has been no recent study on the natural food habits of brown bears (Ursus arctos) or the influence of artificial feeding sites on their diet. During 2017, we collected 53 brown bear stomachs from bears in 2 regions of Croatia— Gorski Kotar and Lika—to assess their diet. Plants—Allium ursinum, the Poaceae family, Cornus mas, berries (i.e., Prunus avium, Rubus plicatus), beechnuts (Fagus spp.)—and various plant parts (i.e., dry leaves, buds, conifer needles, and twigs), as well as mushrooms, made up 80% of the percentage of the volume (%V) of all consumed items. Corn (Zea mays) from the feeding sites made up 37% of the bears’ diet (%V), whereas 20% (%V) was meat and 14% (%V) was pome fruits. Scavenged or preyed animal species, such as wild boar (Sus scrofa), horse (Equus caballus), domestic pig (S. scrofa domesticus), cattle (Bos taurus), roe deer (Capreolus capreolus), and small mammals comprised >66% of %FO (frequency of occurrence), but only 20% of %V. Our results showed that food resources (i.e., livestock such as horses, cattle, and pigs, and corn) found at supplemental feeding sites were more frequently chosen by bears than natural food in 2017, a year characterized by almost no beechnut crop. The results showed that subadult bears obtained most food from feeding sites. These 2 patterns suggested that bears may focus on artificial feeding sites to find food in years when natural food sources are depleted, although this should be tested using diet and food availability data collected from several years.